2014 International Conference on Lightning Protection (ICLP) 2014
DOI: 10.1109/iclp.2014.6973281
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of measured lightning electric fields observed in Malaysia

Abstract: This paper presents a characteristic of lightning electric fields. The lightning electric fields captured by two parallel plats sensor and the characterization for preliminary breakdown pulse (PBP) and first return stroke (RS) were studied. A total of 207 data were recorded and 10 data are selected and been utilized in this paper accordingly. In PBP signal data, time before return stroke, ending time and maximum peak of PBP were analyzed. The time duration between the PBP and the occurrence of RS was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The average slow front duration in this study is around 4.75 µs. The result here is similar to those reported in other studies in Malaysia, which capture the average slow front duration at around 4.95 µs [18], and 4.50 µs [20].…”
Section: Ice4ct2021supporting
confidence: 91%
See 1 more Smart Citation
“…The average slow front duration in this study is around 4.75 µs. The result here is similar to those reported in other studies in Malaysia, which capture the average slow front duration at around 4.95 µs [18], and 4.50 µs [20].…”
Section: Ice4ct2021supporting
confidence: 91%
“…This indicate that the PBPs will preceded the first return stroke by around 9.44 ms in average. The time obtain in this paper is very close when comparing the result with CL Wooi [18], which report the average PBPs to return stroke is around 10.5 ms. This time range is a good reference as a parameter for the engineer to design the relay to protect the electronic equipment.…”
Section: Ice4ct2021supporting
confidence: 76%
“…(2014), Arshad et al. (2014), and Hazmi et al. (2016) found AM values between 8 and 58 ms, in tropical regions.…”
Section: Resultsmentioning
confidence: 87%
“…Figure 3a shows the histogram of PB-RS intervals. Baharudin et al (2012), , Arshad et al (2014), andHazmi et al (2016) found AM values between 8 and 58 ms, in tropical regions. In most studies in tropical regions, the AM is shorter than 30 ms, this could be related to the pre-trigger used in different studies, we speculate that studies that use long pre-trigger are more likely to record longer PB-RS intervals.…”
Section: Preliminary Breakdown Pulse Train Characteristicsmentioning
confidence: 90%
“…Comparative studies about the lightning discharge processes in different meteorological conditions can contribute to stablish the return strokes characteristics and provide a better understanding of the lightning phenomena [4], [10]- [12]. However, there are only a few measurements done in the tropical regions (Sri Lanka, Malaysia and Indonesia).…”
Section: Introductionmentioning
confidence: 99%